Growth axis maturation is linked to nutrition, growth and developmental rate. (15th August 2015) - Hetz, Jennifer A.; Menzies, Brandon R.; Shaw, Geoffrey; Rao, Alexandra; Clarke, Iain J.; Renfree, Marilyn B.
Highlights: Marsupials give birth to altricial young developmentally similar to fetal eutherians. Nutritional intake of pouch young can be easily manipulated. Enhanced nutrition of the pouch young increases growth factor production in the liver and growth. Accelerated growth results in earlier growth axis maturation. Graphical Abstract: Abstract: Maturation of the mammalian growth axis is thought to be linked to the transition from fetal to post-natal life at birth. However, in an altricial marsupial, the tammar wallaby ( Macropus eugenii ), this process occurs many months after birth but at a time when the young is at a similar developmental stage to that of neonatal eutherian mammals. Here we manipulate growth rates and demonstrate in slow, normal and fast growing tammar young that nutrition and growth rate affect the time of maturation of the growth axis. Maturation of GH/IGF-I axis components occurred earlier in fast growing young, which had significantly increased hepatic GHR, IGF1 and IGFALS expression, plasma IGF-I concentrations, and significantly decreased plasma GH concentrations compared to age-matched normal young. These data support the hypothesis that the time of maturation of the growth axis depends on the growth rate and maturity of the young, which can be accelerated by changing their nutritional status.